SIV vpx is essential for macrophage infection but not for development of AIDS. - Susan V Westmoreland; A Peter Converse; Kasia Hrecka; Mollie Hurley; Heather Knight; Michael Piatak; Jeffrey Lifson; Keith G Mansfield; Jacek Skowronski; Ronald C Desrosiers (PLoS ONE)
Analysis of rhesus macaques infected with a vpx deletion mutant virus of simian immunodeficiency virus mac239 (SIVΔvpx) demonstrates that Vpx is essential for efficient monocyte/macrophage infection in vivo but is not necessary for development of AIDS. To compare myeloid-lineage cell infection in monkeys infected with SIVΔvpx compared to SIVmac239, we analyzed lymphoid and gastrointestinal tissues from SIVΔvpx-infected rhesus (n = 5), SIVmac239-infected rhesus with SIV encephalitis (7 SIV239E), those without encephalitis (4 SIV239noE), and other SIV mutant viruses with low viral loads (4 SIVΔnef, 2 SIVΔ3). SIV+ macrophages and the percentage of total SIV+ cells that were macrophages in spleen and lymph nodes were significantly lower in rhesus infected with SIVΔvpx (2.2%) compared to those infected with SIV239E (22.7%), SIV239noE (8.2%), and SIV mutant viruses (10.1%). In colon, SIVΔvpx monkeys had fewer SIV+ cells, no SIV+ macrophages, and lower percentage of SIV+ cells that were macrophages than the other 3 groups. Only 2 SIVΔvpx monkeys exhibited detectable virus in the colon. We demonstrate that Vpx is essential for efficient macrophage infection in vivo and that simian AIDS and death can occur in the absence of detectable macrophage infection.